Internet-assisted delivery of cognitive behavioural therapy (CBT) for childhood anxiety: Systematic review and meta-analysis. (January 2015) - Rooksby, Maki; Elouafkaoui, Paula; Humphris, Gerry; Clarkson, Jan; Freeman, Ruth
Highlights: CBT, delivered via online programmes is effective for child anxiety disorders. Children and their families found CBT online programmes acceptable and satisfactory. The domain will benefit from more randomised controlled trials with follow-ups. Future studies should include health economic evaluation of delivering CBT online. Abstract: Aim: To conduct a systematic review and meta-analysis of the literature to assess efficacy of internet-delivered cognitive behavioural therapy (CBT) for child anxiety disorder. Method: A systematic search of 7 electronic databases was conducted to assess CBT intervention for children with anxiety problems with remote delivery either entirely or partly via technology. Six articles reporting 7 studies were included. Results: The findings together suggested that CBT programmes involving computerised elements were well received by children and their families, and its efficacy was almost as favourable as clinic-based CBT. The mixture of children and adolescents included the studies, diverse range of programmes, and lack of consistency between study designs made it difficult to identify key elements of these programmes or draw conclusions on the treatment efficacy. Conclusions: Analysis supports online delivery for wider access of this evidence-based therapy. Areas in need of improvement for this new method are indicated.